CORPORATE SOCIAL RESPONSIBILITY AS CONDITION OF INCLUDING UKRAINE IN EUROPE AND WORLD ECONOMIC SPACE - T. Lytvynenko (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The thesis that companies’ activities for introduction of corporate social responsibility stimulates the speed of to the processes of the technical upgrade, modernization of company’s activity and increase of its profitability is proved within the article. Those Ukrainian companies, which have high index of activities transparency, are also the most profitable. However, we can’t observe any significant increment of number of companies joining the Global agreement. One of the explanations we could name is the unproved idea supported by some politicians and economists about a shadow (‘black’) market that allegedly allows creating workplaces and taking off social tension in society on the certain stage. Insignificant values of index of citizens’ trust to activity of industries holds on the development socially of responsible business. Trust considered as a part of the general social capital. The Government of Ukraine must support initiative of companies to introduce social responsibility of business, as many European governments do it. It is also important to inform society of advantages of CSR.